Collaboration Analysis of Semarang City Dengue Hemorrhagic Fever Health Surveillance Officer with Social Network Analysis - Santoso, Lukman; Manongga, Danny; Iriani, Ade (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
This study aims to determine the pattern of a network collaboration between dengue hemorrhagic health surveillance personnel in the city of Semarang and to understand the flow of information deeply. The method of social network analysis / SNA (Social Network Analysis) on formal and informal communication networks between surveillance officers aims to produce sociometry and sociogram data so that the centrality of each actor in the network can be known. Interaction between Officers will be known through the analysis of the centrality of levels (degree), closeness (closeness), and intercession (betweenness). The approach used is descriptive quantitative. Data was collected using a research instrument in the form of a questionnaire, while the process of input and data analysis was carried out by looking at intact networks and ego networks carried out using UCINET. The results of the analysis show that officers dominate the centrality of the level and the intermediary with the position of Coordinator both City and District (Id. # 128, # 1, # 2, # 3). Collaboration based on working areas has a strong bond because 71% of the districts have a network density above 50%. While the value of closeness is dominated by surveillance members with id # 54, # 15, # 2, # 214, # 15 and # 10.